Layered transparent back contact structure for cadmium telluride film power generation glass and preparation method and application of layered transparent back contact structure
By using a layered transparent back contact structure with AlGaOx passivation layer, Ti3C2TxMXene intermediate layer and transparent crack film photolithography templated nanogrid electrode layer on the cadmium telluride thin film power generation glass, the shortcomings of the back contact structure in the prior art are solved, the power generation efficiency and double-sided performance are improved, and it is suitable for the fields of integrated building photovoltaics and other fields.
Patent Information
- Application Number
- CN202411728371.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-25
AI Technical Summary
The back contact structure of the existing cadmium telluride thin film power generation glass has electronic defects, rapid carrier recombination, difficulty in forming transparent p-type contacts, and difficulty in meeting the requirements of high transmittance, high conductivity and low series resistance, and the double-sided power generation performance is poor.
A layered transparent back contact structure is adopted, including AlGaOx passivation layer, Ti3C2TxMXene intermediate layer and transparent crack film lithography templated nanogrid electrode layer, and these layers are deposited by spin coating and drop casting to form an efficient back contact structure.
It improves the power generation efficiency and double-sided performance of cadmium telluride thin film power generation glass, achieves high transmittance, high conductivity and low series resistance, and is suitable for integrated building photovoltaics and other fields.
Smart Images

Figure CN119894167A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaic technology, and in particular to a layered transparent back contact structure for cadmium telluride thin-film power generation glass, and a preparation method and application thereof. Background Art
[0002] Current status and development trend of cadmium telluride thin-film power generation glass industry As a new type of photovoltaic product, cadmium telluride thin-film power generation glass has unique advantages, such as customization, good weak light performance, and beautiful appearance, and has broad application prospects in the fields of building integrated photovoltaics (BIPV). With the continuous development of photovoltaic technology, improving the power generation efficiency and double-sided performance of cadmium telluride thin-film power generation glass has become a key demand for the development of the industry.
[0003] The back contact structure of cadmium telluride thin-film power generation glass has a significant impact on its performance. The current back contact technology has some problems, such as rapid carrier recombination caused by electronic defects and charged species on the back surface, difficulty in forming ohmic contact with transparent p-type contact, and difficulty in meeting the requirements of high transmittance, high conductivity and low series resistance. In terms of double-sided power generation performance, the existing cadmium telluride thin-film power generation glass technology has not yet achieved efficient double-sided contact, limiting its efficiency improvement in some application scenarios that require double-sided lighting and power generation.
[0004] Limitations of existing related research Although there have been some studies on the double-sided structure of cadmium telluride, such as ultra-thin sputtering, carbon nanotube contact, nanoparticle solution contact, and doped and alloyed metal oxide contact, these methods still have some limitations when applied to cadmium telluride thin-film power generation glass, such as difficulties in carrier extraction of thicker devices and less than ideal contact material performance. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a layered transparent back contact structure for cadmium telluride thin film power generation glass, and a preparation method and application thereof.
[0006] In a first aspect, the present invention provides a layered transparent back contact structure for cadmium telluride thin film power generation glass, the layered transparent back contact structure comprising an AlGaOx passivation layer, a Ti3C2T x MXene interlayer and transparent crack film photolithography templated nanogrid electrode layer.
[0007] Furthermore, the gold nano-grids in the transparent crack film photolithography templated nano-grid electrode layer are embedded in the crack film photolithography template.
[0008] In a second aspect, the present invention provides a method for preparing a layered transparent back contact structure for cadmium telluride thin film power generation glass according to any one of the first aspects, the preparation method comprising the following steps:
[0009] AlGaOx is deposited on the cadmium telluride film by spin coating to form an AlGaOx passivation layer;
[0010] Ti3C2T is deposited on the AlGaOx passivation layer by spin coating. x MXene, forming Ti3C2T x MXene interlayer;
[0011] The Ti3C2T x A crack film photolithography template is deposited on the MXene intermediate layer, which is then placed in a thermal evaporation system for power generation glass to evaporate gold, nickel and aluminum in sequence to form a transparent crack film photolithography templated nano-grid electrode layer to obtain the layered transparent back contact structure.
[0012] Furthermore, the step of depositing AlGaOx on the cadmium telluride film by spin coating to form an AlGaOx passivation layer includes the following process:
[0013] On the cadmium telluride film, the AlGaOx precursor solution is first evenly spread by a low-speed spin coating method of 800-1000 rpm, and then the rotation speed is increased to 2400-2600 rpm to form a uniform film; thereafter, the precursor is converted into a stable AlGaOx film through a high-temperature annealing treatment to form the AlGaOx passivation layer.
[0014] Furthermore, the working condition parameters of the high temperature annealing treatment include: a temperature of 210 to 230° C. and a time of 15 to 30 minutes.
[0015] Furthermore, Ti3C2T is deposited on the AlGaOx passivation layer by spin coating. x MXene, forming Ti3C2T x The steps of MXene interlayer include the following process:
[0016] On the AlGaOx passivation layer, Ti3C2T x The MXene solution is first evenly spread by a low-speed spin coating method of 800-1000 rpm, and then the speed is increased to 2400-2600 rpm to form a uniform middle layer; then, it is dried at 80-100 ° C for 1-2 hours to form the Ti3C2T x MXene interlayer.
[0017] Furthermore, the Ti3C2T xA crack film photolithography template is deposited on the MXene intermediate layer, and then placed in a thermal evaporation system of the power generation glass to evaporate gold, nickel and aluminum in sequence to form a transparent crack film photolithography template nano-grid electrode layer. The steps of obtaining the layered transparent back contact structure include the following processes:
[0018] In the Ti3C2T x On the MXene middle layer, 25-30uLTiO2 solution is drop-casted on each square centimeter of the chip to deposit a crack film lithography template. After the drop-casting is completed, the sample is placed in a drying oven and dried overnight at room temperature to form a crack film lithography template;
[0019] Place the device with the crack film lithography template into the vacuum chamber of the thermal evaporation system and evacuate the vacuum to less than 10 - 3 Pa;
[0020] First, evaporate gold, control the evaporation rate of gold to 0.1-0.3nm / s, and the evaporation thickness to 20-80nm. After evaporation, gold will be deposited at the cracks of the crack film lithography template to form nanoscale gold lines;
[0021] Then, nickel is evaporated, the evaporation rate of nickel is controlled at 0.05-0.1 nm / s, and the evaporation thickness is 100 nm;
[0022] Finally, aluminum is evaporated at a rate of 0.2-0.4 nm / s and a thickness of 1 μm to form a transparent crack film photolithography template nanogrid electrode layer. The gold nanogrid is embedded in the crack film photolithography template and is bonded to the Ti3C2T x The MXene intermediate layer and the AlGaOx passivation layer together constitute the complete layered transparent back contact structure.
[0023] In a third aspect, the present invention provides the use of the layered transparent back contact structure for cadmium telluride thin film power generation glass described in any one of the first aspects and / or the layered transparent back contact structure prepared by the preparation method described in any one of the second aspects in the preparation of cadmium telluride thin film.
[0024] In a fourth aspect, the present invention provides a cadmium telluride thin film, comprising the layered transparent back contact structure for cadmium telluride thin film power generation glass described in any one of the first aspects and / or the layered transparent back contact structure prepared by the preparation method described in any one of the second aspects.
[0025] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:
[0026] The embodiment of the present invention provides a layered transparent back contact structure for cadmium telluride thin film power generation glass and a preparation method and application thereof. In the present invention, the AlGaOx passivation layer can increase the open circuit voltage and adjust the band gap, but the in-plane series resistance is high; Ti3C2T x MXene intermediate layer has high conductivity and adjustable work function, and can form ohmic contact with AlGaOx; Ti3C2T x The MXene intermediate layer has low cost and can increase macroscopic conductivity. The three work together to address the shortcomings of the existing cadmium telluride thin-film power generation glass back contact technology, improve its power generation efficiency and double-sided performance, and have broad application prospects in the cadmium telluride industry, building-integrated photovoltaics and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0029] Figure 1 A schematic diagram of a layered transparent back contact structure for cadmium telluride thin film power generation glass provided in an embodiment of the present invention; wherein: 1-transparent crack film photolithography template nano-grid electrode layer; 2-Ti3C2T x MXene intermediate layer; 3-AlGaOx passivation layer. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0032] In a first aspect, the present invention provides a layered transparent back contact structure for cadmium telluride thin film power generation glass, such as Figure 1 As shown ( Figure 1Middle: 1-transparent crack film lithography template nanogrid electrode layer; 2-Ti3C2T x MXene intermediate layer; 3-AlGaOx passivation layer), the layered transparent back contact structure includes an AlGaOx passivation layer, a Ti3C2T x MXene interlayer and transparent cracked film lithography (CFL) templated nanomesh electrode layer.
[0033] The AlGaOx passivation layer has good band alignment with the back surface of the CdTe film, which can improve the open circuit voltage. Its solution-processed nature allows the band gap to be tuned according to the ratio of aluminum and gallium precursors. However, it has its own high in-plane series resistance problem and cannot be used as a final contact layer alone, and it reduces the fill factor when combined with the CFL templated nanogrid.
[0034] The Ti3C2TxMXene layer has high conductivity (up to 20,000S / cm), a hydrophilic surface, and an adjustable chemical composition. Its work function can be adjusted by controlling the transition metal and surface termination, and it matches well with cadmium telluride. As an intermediate layer, it can form a transparent ohmic contact with the AlGaOx buffer layer, reduce series resistance, improve micron-scale lateral conductivity, and provide a lateral conduction path for carriers to enter the nanogrid.
[0035] CFL templated nanogrids: The spontaneous formation of crack networks when colloidal solutions dry is used to fabricate metal nanogrids, which have the advantages of low cost and fast fabrication. x The CFL-patterned gold nanogrid is mounted on the MXene layer to increase the macroscopic in-plane conductivity while maintaining high transparency.
[0036] In a second aspect, the present invention provides a method for preparing a layered transparent back contact structure for cadmium telluride thin film power generation glass according to any one of the first aspects, the preparation method comprising the following steps:
[0037] 1. Deposition of AlGaOx on CdTe film by spin coating:
[0038] First, add an appropriate amount of AlGaOx precursor solution (187 mg of Al(NO3)3·9H2O and 77 mg of Ga(NO3)3·
[0039] xH2O was added to 10mL of DMF (concentration: 0.1191M--0.1211M; dosage: 200-300ml) and added dropwise to the surface of the rotating cadmium telluride film, and the initial spin coating was performed at a relatively low speed of 1000rpm for 10s to spread the solution evenly on the surface of the cadmium telluride film to avoid agglomeration or uneven distribution of the solution.
[0040] Then the rotation speed was increased to 2500rpm for high-speed spin coating for 50 seconds. The centrifugal force generated by high-speed rotation made the solution form a uniform film. After the spin coating was completed, the sample was annealed at a high temperature of 220°C for 20 minutes. During the annealing process, the AlGaOx precursor reacted chemically to form a stable AlGaOx film, while optimizing the crystal structure of the film, reducing defects, and improving its electrical properties and the interface bonding quality with the cadmium telluride film.
[0041] 2. Deposition of Ti3C2T on AlGaOx passivation layer x MXene and drying:
[0042] Dilute Ti3C2T to a concentration of 4-6 mg / ml x The MXene solution was added to the surface of the AlGaOx passivation layer in the same spin coating manner, and the spin coating operation was performed to ensure that the Ti3C2T x The MXene layer evenly covers the AlGaOx passivation layer to form a continuous and uniform intermediate layer.
[0043] 3. After spin coating, place the sample in a vacuum oven to dry at 80-100°C for 1-2 hours to accelerate the evaporation of the solvent and avoid contamination of the film by impurities in the air to ensure the Ti3C2T x The MXene layer is tightly bonded to the AlGaOx passivation layer to form a good ohmic contact.
[0044] 4. Deposit the crack film photolithography template by drop casting and dry overnight:
[0045] 27.9uL TiO2 solution was drop-casted on each square centimeter of the chip to deposit a crack film lithography template. After the drop-casting was completed, the sample was placed in a room temperature drying oven and dried overnight at room temperature to allow the solvent in the template solution to fully evaporate and the polymer material to form a stable crack network structure, namely the crack film lithography template.
[0046] 5. Place the device into a thermal evaporation system suitable for power generation glass, and evaporate gold, nickel, and aluminum in sequence to form a CFL templated nano-grid electrode:
[0047] Place the device with the crack film lithography template into the vacuum chamber of the thermal evaporation system and evacuate the vacuum to less than 10 - 3 Pa, in order to reduce the interference of gas impurities in the evaporation process.
[0048] First, gold is evaporated, and the evaporation rate of gold is controlled at 0.1-0.3nm / s and the evaporation thickness is 20-80nm. After evaporation, gold will be deposited at the cracks of the crack film lithography template to form nanoscale gold lines as the main conductive channel.
[0049] Then nickel is evaporated, the evaporation rate of nickel is controlled at 0.05-0.1 nm / s, and the evaporation thickness is 100 nm. Nickel mainly plays the role of improving the adhesion and stability between gold and other layers.
[0050] Finally, aluminum is evaporated at a rate of 0.2-0.4 nm / s and a thickness of 1 um. Aluminum can further improve the conductivity and stability of the electrode, while also protecting the entire structure. After evaporation, a CFL templated nanogrid electrode is formed, with the gold nanogrid embedded in the crack film lithography template, forming a complete layered transparent back contact structure together with the Ti3C2TxMXene layer and the AlGaOx passivation layer.
[0051] It should be noted that the layered transparent back contact structure for cadmium telluride thin-film power generation glass provided in the embodiments of the present invention, and the component raw materials involved in the preparation method and application thereof, unless otherwise specified or specified, can be directly commercially available products or homemade using existing public preparation methods; at the same time, the steps and parameters involved, unless otherwise specified or specified, can be carried out according to existing processing techniques or directly using existing equipment, and the present invention document will not describe them one by one.
[0052] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0053] Example 1
[0054] This example provides a layered transparent back contact structure for cadmium telluride thin film power generation glass, the layered transparent back contact structure includes an AlGaOx passivation layer, a Ti3C2T x MXene intermediate layer and transparent crack film photolithography template nano-grid electrode layer; the preparation method of the layered transparent back contact structure for cadmium telluride thin film power generation glass comprises the following steps:
[0055] 1. Deposit AlGaOx on the CdTe film by spin coating to form an AlGaOx passivation layer:
[0056] First, add an appropriate amount of AlGaOx precursor solution (the AlGaOx precursor solution is prepared by adding 187 mg of Al(NO3)3·9H2O and 77 mg of Ga(NO3)3·xH2O to 10 mL of DMF; concentration 0.1200 M; dosage 250 ml) dropwise onto the surface of the rotating cadmium telluride film, and perform preliminary spin coating at a relatively low speed of 1000 rpm for 10 seconds to spread the solution evenly on the surface of the cadmium telluride film to avoid agglomeration or uneven distribution of the solution; then The high speed spin coating is performed at 2500rpm for 50 seconds. The centrifugal force generated by the high-speed rotation makes the solution form a uniform film. After the spin coating is completed, the sample is annealed at a high temperature of 220°C for 20 minutes. During the annealing process, the AlGaOx precursor undergoes a chemical reaction to form a stable AlGaOx film. At the same time, the crystal structure of the film is optimized, defects are reduced, its electrical properties and the interface bonding quality with the cadmium telluride film are improved, and an AlGaOx passivation layer is formed.
[0057] 2. Deposition of Ti3C2T on AlGaOx passivation layer x MXene and dried to form Ti3C2T x MXene interlayer:
[0058] Ti3C2T was diluted to a concentration of 5 mg / ml. x The MXene solution was added to the surface of the AlGaOx passivation layer in the same spin coating manner, and the spin coating operation was performed to ensure that the Ti3C2T x The MXene layer is evenly covered on the AlGaOx passivation layer to form a continuous and uniform intermediate layer. After the spin coating is completed, the sample is placed in a vacuum oven for drying. The drying temperature is set at 90 ° C and the drying time is 1.5 hours to accelerate the evaporation of the solvent and avoid contamination of the film by impurities in the air to ensure the Ti3C2T x The MXene layer is tightly combined with the AlGaOx passivation layer to form a good ohmic contact, forming a Ti3C2T x MXene interlayer.
[0059] 3. Deposit the crack film photolithography template by drop casting and dry overnight:
[0060] 27.9uL of TiO2 solution was drop-casted on each square centimeter of the chip obtained in step 2 to deposit a crack film photolithography template. After the drop-casting was completed, the sample was placed in a room temperature drying oven and dried overnight at room temperature to allow the solvent in the template solution to fully evaporate and the polymer material to form a stable crack network structure, i.e., a crack film photolithography template;
[0061] 4. Place the device obtained in step 3 into a thermal evaporation system suitable for power generation glass, and evaporate gold, nickel and aluminum in sequence to form a CFL templated nano-grid electrode:
[0062] Place the device with the crack film lithography template into the vacuum chamber of the thermal evaporation system and evacuate the vacuum to less than 10 - 3 Pa, to reduce the interference of gas impurities during the evaporation process;
[0063] First, gold is evaporated, and the evaporation rate of gold is controlled at 0.2nm / s and the evaporation thickness is 40nm. After evaporation, gold will be deposited at the cracks of the crack film lithography template to form nanoscale gold lines as the main conductive channel;
[0064] Next, nickel is evaporated. The evaporation rate of nickel is controlled at 0.08 nm / s and the evaporation thickness is 100 nm. Nickel mainly plays a role in improving the adhesion and stability between gold and other layers.
[0065] Finally, aluminum is evaporated at a rate of 0.3nm / s and a thickness of 1um. Aluminum can further improve the conductivity and stability of the electrode, while also protecting the entire structure. After evaporation, a CFL templated nanogrid electrode is formed. The gold nanogrid is embedded in the crack film lithography template, and together with the Ti3C2TxMXene layer and the AlGaOx passivation layer, a complete layered transparent back contact structure is formed, and finally a layered transparent back contact structure for cadmium telluride thin film power generation glass is obtained.
[0066] Test Example 1
[0067] In this example, the performance of the layered transparent back contact structure for cadmium telluride thin film power generation glass obtained in Example 1 was tested. The cadmium telluride thin film deposited on the TCO substrate was selected as the substrate. The layered transparent back contact structure was prepared according to the above-mentioned preparation method. After the subsequent cadmium telluride power generation glass preparation process, AlGaOx+Ti3C2T x The performance of the cadmium telluride thin-film power generation glass device with +CFL gold contact structure is significantly better than the existing ordinary cadmium telluride components. Under 1 sun illumination, the front power generation efficiency can reach 19.5%, and the back power generation efficiency is 2.8%-2.9%. The filling factor is significantly improved compared with other structures, eliminating the flip characteristics related to the back contact barrier. Under double-sided illumination conditions, when the back illumination is 10% AM1.5G, the device generates more than 200W / m 2 The increase in fill factor has a more significant impact on power generation than the increase in short-circuit current density; when the back illumination is 40% AM1.5G, the power generation reaches 213W / m 2This layered structure can effectively solve the problems faced by the back contact of cadmium telluride thin-film power generation glass, improve its power generation efficiency and double-sided performance, and thus enhance the application value of cadmium telluride thin-film power generation glass in fields such as building-integrated photovoltaics.
[0068] Test Example 2
[0069] In this example, the performance of the layered transparent back contact structure for cadmium telluride thin film power generation glass obtained in Example 1 was tested. Compared with the traditional cadmium telluride battery, the performance was greatly improved. The following Table 1 gives a performance comparison between the layered transparent back contact layer cadmium telluride battery and the prior art CdTe:Cu cadmium telluride thin film solar cell.
[0070] Table 1
[0071]
[0072] From the data in Table 1, we can see that the cadmium telluride thin-film solar cells using the layered transparent back contact layer technology have been improved in multiple key indicators, demonstrating the potential of the layered transparent back contact layer technology in improving the performance of CdTe thin-film solar cells, and also indicating that the technology has broad application prospects in commercial production. By optimizing the electrical performance of the cell, this technology is expected to bring innovation and competitiveness to the solar cell market.
[0073] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0074] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A layered transparent back contact structure for cadmium telluride thin film power generation glass, characterized in that: The layered transparent back contact structure includes an AlGaOx passivation layer, a Ti3C2T x MXene interlayer and transparent crack film photolithography templated nanogrid electrode layer.
2. The layered transparent back contact structure for cadmium telluride thin film power generation glass according to claim 1, characterized in that: The gold nano-grid in the transparent crack film photolithography templated nano-grid electrode layer is embedded in the crack film photolithography template.
3. A method for preparing a layered transparent back contact structure for cadmium telluride thin film power generation glass according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: AlGaOx is deposited on the cadmium telluride film by spin coating to form an AlGaOx passivation layer; Ti3C2T is deposited on the AlGaOx passivation layer by spin coating. x MXene, forming Ti3C2T x MXene interlayer; The Ti3C2T x A crack film photolithography template is deposited on the MXene intermediate layer, which is then placed in a thermal evaporation system for power generation glass to evaporate gold, nickel and aluminum in sequence to form a transparent crack film photolithography templated nano-grid electrode layer to obtain the layered transparent back contact structure.
4. The method for preparing a layered transparent back contact structure for cadmium telluride thin film power generation glass according to claim 3, characterized in that: The steps of depositing AlGaOx on the cadmium telluride film by spin coating to form an AlGaOx passivation layer include the following processes: On the cadmium telluride film, the AlGaOx precursor solution is first evenly spread by a low-speed spin coating method of 800-1000 rpm, and then the rotation speed is increased to 2400-2600 rpm to form a uniform film; thereafter, the precursor is converted into a stable AlGaOx film through a high-temperature annealing treatment to form the AlGaOx passivation layer.
5. The method for preparing a layered transparent back contact structure for cadmium telluride thin film power generation glass according to claim 4, characterized in that: The working condition parameters of the high temperature annealing treatment include: a temperature of 210 to 230° C. and a time of 15 to 30 minutes.
6. The method for preparing a layered transparent back contact structure for cadmium telluride thin film power generation glass according to claim 3, characterized in that: Ti3C2T is deposited on the AlGaOx passivation layer by spin coating. x MXene, forming Ti3C2T x The steps of MXene interlayer include the following process: On the AlGaOx passivation layer, Ti3C2T x The MXene solution is first evenly spread by a low-speed spin coating method of 800-1000 rpm, and then the speed is increased to 2400-2600 rpm to form a uniform middle layer; then it is dried at 80-100 ° C for 1-2 hours to form the Ti3C2T x MXene interlayer.
7. The method for preparing a layered transparent back contact structure for cadmium telluride thin film power generation glass according to claim 3, characterized in that: The Ti3C2T x A crack film photolithography template is deposited on the MXene intermediate layer, and then placed in a thermal evaporation system of the power generation glass to evaporate gold, nickel and aluminum in sequence to form a transparent crack film photolithography template nano-grid electrode layer. The steps of obtaining the layered transparent back contact structure include the following processes: In the Ti3C2T x On the MXene middle layer, 25-30uLTiO2 solution is drop-casted on each square centimeter of the chip to deposit a crack film lithography template. After the drop-casting is completed, the sample is placed in a drying oven and dried overnight at room temperature to form a crack film lithography template; Place the device with the crack film lithography template into the vacuum chamber of the thermal evaporation system and evacuate the vacuum to less than 10 -3 Pa; First, evaporate gold, control the evaporation rate of gold to 0.1-0.3nm / s, and the evaporation thickness to 20-80nm. After evaporation, gold will be deposited at the cracks of the crack film lithography template to form nanoscale gold lines; Then, nickel is evaporated, the evaporation rate of nickel is controlled at 0.05-0.1 nm / s, and the evaporation thickness is 100 nm; Finally, aluminum is evaporated at a rate of 0.2-0.4 nm / s and a thickness of 1 μm to form a transparent crack film photolithography template nanogrid electrode layer. The gold nanogrid is embedded in the crack film photolithography template and is bonded to the Ti3C2T x The MXene intermediate layer and the AlGaOx passivation layer together constitute the complete layered transparent back contact structure.
8. Use of a layered transparent back contact structure for cadmium telluride thin film power generation glass as claimed in any one of claims 1 to 2 and / or a layered transparent back contact structure prepared by the preparation method as claimed in any one of claims 3 to 7 in the preparation of cadmium telluride thin film.
9. A cadmium telluride thin film, characterized in that: The cadmium telluride thin film comprises the layered transparent back contact structure for cadmium telluride thin film power generation glass as described in any one of claims 1 to 2 and / or the layered transparent back contact structure obtained by the preparation method as described in any one of claims 3 to 7.